2017
DOI: 10.1002/pc.24280
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic reinforcements of epoxy composites with glass fibers and hyperbranched polymers

Abstract: Glass fibers (GFs) and hyperbranched polymers with amino terminal groups (HBPA) were introduced into epoxy/ polyamide system to fabricate high-performance composites. The impact resistance and mechanical characterization of epoxy/HBPA/GFs composites was performed to investigate the effect of GFs in the composites. The composites revealed noticeable improvement in tensile strength, elongation at break, flexural strength as well as impact resistance in comparison with the unmodified and HBPA modified epoxy/polya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…The typical process was similar to our former reports and shown as follows. Glass‐fibers were first treated with an aqueous solution of H 2 O 2 (30wt%) at 105°C for 6 hr and then functionalized by γ ‐aminopropyl triethoxysilane in toluene at 80°C for 24 hr (named as GF‐APS).…”
Section: Methodssupporting
confidence: 89%
“…The typical process was similar to our former reports and shown as follows. Glass‐fibers were first treated with an aqueous solution of H 2 O 2 (30wt%) at 105°C for 6 hr and then functionalized by γ ‐aminopropyl triethoxysilane in toluene at 80°C for 24 hr (named as GF‐APS).…”
Section: Methodssupporting
confidence: 89%
“…There are many published articles on the modification of nano-SiO 2 , carbon nanotubes, carbon fiber, glass fiber, graphene, and other reinforcements by the hyperbranched polymers. However, the modification of the natural plant fiber is mainly concentrated in the textile field and its application in polymer matrix composites is very limited. The effects of various hyperbranched polymers on the modification of different reinforcements are systematically summarized in Table . …”
Section: Modifying Natural Plant Fiber By Hyperbranched Polymermentioning
confidence: 99%
“…Li et al investigated the characteristics of composites made of epoxy/hyperbranched polymers with amino-terminal groups and glass fibers. They found that these composites exhibited significant improvements in impact resistance, elongation at break, and tensile properties compared to composites made with unmodified epoxy/polyamide thermosets [ 26 ]. Rashid et al studied the different methods of 3D-printing biomaterials, which is a popular technique for manufacturing composites [ 27 ].…”
Section: Introductionmentioning
confidence: 99%